Association between joint physical activity and alcohol intake and all-cause mortality in patients with cardiovascular disease: findings from NHANES 2007–2018 - Zhang, Shiyang; Zhuo, Yeji; Zhu, Chunyan; Zhou, Tong; Wang, Zongtao; Zheng, Jianyi; Li, Tudi; Chen, Rong; Lin, Dong; Xie, Zhixin; Fu, Zhenyang; Zeng, Zhihuan; et al. (Frontiers in Nutrition, 2025)
BackgroundPhysical activity and alcohol consumption are both highly prevalent in many countries, while the evidence related to joint effect on physical activity and alcohol consumption on patients with cardiovascular disease (CVD) was still deficient. This study was aimed to investigate the association between joint moderate-to-vigorous physical activity (MVPA) and alcohol intake and all-cause mortality in patients with CVD.MethodsA total of 4,047 participants from the National Health and Nutrition Examination Survey (NHANES) with self-reported CVD history, exercise and alcohol consumption amounts were included this study. Participants were stratified into 12 groups by MVPA level (none/insufficient/sufficient) and alcohol intake (abstainer/light/moderate/heavy). Restricted cubic spline and Cox regression models assessed mortality associations.ResultsMVPA showed an L-shaped association with mortality, while alcohol exhibited a U-shaped pattern. The lowest observed mortality risk occurred in patients with MVPA ≥150 min/week and alcohol consumption 8.4–15.4 drinks/week (HR = 0.348, 95% CI: 0.169–0.667). Comparably lower risk was seen with MVPA <150 min/week plus light alcohol intake (<8.4 drinks/week) (HR = 0.400, 95% CI: 0.267–0.588).ConclusionAmong patients with established CVD, any level of MVPA was associated with survival benefits. The greatest mortality reduction occurred with >150 min/week of MVPA alongside light to moderate alcohol consumption (<15.4 drinks/week). However, comparable survival benefits were observed with <150 min/week of MVPA when coupled with light alcohol intake. MVPA remains the cornerstone for mortality risk reduction in this population.